Development of Thematic Worksheet Based on Character Education for Fifth Graders Schools - Sari Utami, Setia; Sukenda, Asep; Valen, Andri (Journal of Research and Educational Research Evaluation, 2020)
This study aims to develop LKS in the form of Thematic Worksheet Based on Environmental Care Character Education on Theme 8 "Environment of Our Friends" Subtema 3 "Environmental Conservation Efforts" for fifth grade students of SD Negeri 15 Lubuklinggau and to find out the quality of LKS seen from the validity and practical aspects. This research is a development research with 4D development model (four D model). Data collection techniques in the study are interviews and questionnaires / questionnaires. The data analysis technique uses a Likert scale. The results showed that: (1) The validity of the worksheet showed that the worksheets developed were included in the Valid classification of the language worthiness component with an average score of 3.00, the content eligibility component was included in the Valid classification with an average score of 3.23 , and the presentation eligibility component is included in the Valid classification with an average score of 3.07. (2) the quality of teaching materials seen from the aspect of practicality included in the classification of "Very Practical" with an average score of 4.50 determined based on the results of students' questionnaire responses to worksheets.